KEBIJAKAN PENYELENGGARAAN MADRASAH ALIYAH KEJURUAN - Safitri, Nita Andriani; Marlina, Rina (Madrasa: Journal of Islamic Educational Management, 2019)
This paper aims to uncover the implementation of the policy of vocational madrasah aliyah (MAK) in Indonesia. The research method used in the study was qualitative. Data was collected through interviews, observations and documentation studies. The results showed that the existence of MAK was considered legal. This was marked by the issuance of the Minister of Religion Affair (PMA) Republic of Indonesia No. 60 of 2015. In its implementation, the establishment of MAK focused on MAK as public school which is outside of Java Island such as North Sulawesi and Riau. The implementation of the pilot project was implemented in 2019, because until 2018 the building of MAKN as national pilot project was just completed. Some foundations or private parties tried to set up MAK but failed due to lack of funds. So they lacked interest. Therefore, the Ministry of Religion of the Republic of Indonesia, through the Madrasah Director needs to product regulations that the community or foundation does not rush to establish MAK. There are needs to be strategic planning to establish MAK.